A new scoring system for use in capture–recapture studies for bowhead whales photographed with drones1 - William R. Koski; Brent G. Young (Drone Systems and Applications, 2022)
Effective management of animal populations requires knowledge of life history parameters and estimates of population abundance. One method commonly used to estimate abundance is capture–recapture analyses of photographs. Small, relatively inexpensive, rotary-wing drones have become an effective platform for obtaining high-quality aerial photographs of whales. To conduct capture–recapture analyses the animal needs to be defined as marked or unmarked and the photographs must be of high quality. While a system for scoring quality and markedness has previously been developed for bowhead whales (Balaena mysticetus Linnaeus, 1758) (Rugh et al. 1998. Rep. int. Whal. Commn. 48: 501–512), a revised scoring system was needed to incorporate increased information in photographs taken by drones. We present a revised scoring system that enlarges two of the previously defined areas of the whale examined for markings and incorporates smaller markings into the definition of marked whales. We scored 30 whales using the previous criteria and the revised criteria developed in this paper. More whales were identified as marked (23%) and mark scores were higher for 30% of the zones scored using the new system. Increasing the number of marked whales during capture–recapture studies increases the precision of estimated parameters and permits us to make those estimates with smaller samples of photographs.